Potential clinical application of the cancer antigen CA‑62 for differential diagnosis of prostate cancer and benign prostatic hyperplasia at the elevated prostate‑specific antigen - Zh. R. Cherkasova; S. A. Tsurkan; A. I. Prostyakova; A. M. Boroda; A. A. Rozhkov; Yu. N. Pirogova; N. M. Nikitina; M. I. Sekacheva (Исследования и практика в медицине, 2023)
Purpose of the study. Evaluation of the diagnostic characteristics of the CA‑62 marker for epithelial carcinomas for detecting early‑stage prostate cancer in a double‑blind clinical study. This study is also focused on the possibility of using the CA‑62 antigen as an auxiliary tool for decision‑making in prostate cancer diagnosis.Patients and methods. A blinded clinical study was conducted on 325 clinically verified blood serum samples. This includes 144 prostate cancer samples, 79 generally healthy volunteers‑men and 102 samples from patients with benign prostatic hyperplasia (BPH). Quantitative determination of the total and free prostate specific antigen (PSA) levels, as well as the CA‑62 marker of serum samples was performed using the electrochemiluminescent immunoassay ECLIA Elecsys Total and Free PSA (COBAS, Roche Diagnostics GmbH, Germany, EU) and the chemiluminescent immunoassay CLIA‑CA‑62 (JVS Diagnostics LLC, Moscow, RF).Results. A comparison of the CA‑62 level with the results for total and free PSA, as well as other diagnostic methods (PCA3, PHI) for the analysis of the BPH and prostate cancer groups was performed. The results show that the CA‑62 marker has the highest PPV (94.4 %) and NPV (93.1 %). This may increase the reliability of the decision related to the presence of PC and be used by doctors as an argument as an argument for a prostate biopsy referral. It has been demonstrated that using the novel cancer marker CA‑62 makes it possible to detect up to 90 % of the early‑stage prostate cancer with 97.2 % specificity (AUC = 0.969).Conclusion. Using the CA‑62 marker as an auxiliary diagnostic method within the PSA “grey zone” (from 2.5 to 10 ng/ml) made it possible to significantly increase the accuracy of detecting the PC early stages at biopsy up to 93.1 %. It will help the doctors to effectively differentiate between prostate cancer and benign prostatic hyperplasia.